The Concept of Language and the Pursuit of Knowledge in Perspective of Buddhist Philosophy - Phrakrupariyatratanakhunpundit; Kaenwong, Phanutouch (Mahachula Academic Journal, 2025)
In Buddhist philosophy, the concept of language and the pursuit of knowledge are grounded in the direct experience perceived through the senses. Language serves as a means of expressing or communicating our experiences, guiding us toward true knowledge. This knowledge must convey truth and undergo verification to gain acceptance, allowing it to be practically applied for genuine well-being. The approach outlined in the Kalama Sutta exemplifies this process of knowledge validation, where one is encouraged to perceive and investigate through personal experience, applying yonisomanasikara, a method of critical reflection and synthesis. This approach ensures confidence in knowledge as true understanding according to Buddhist philosophy.